2012
DOI: 10.1083/jcb.201107042
|View full text |Cite
|
Sign up to set email alerts
|

Tension is required but not sufficient for focal adhesion maturation without a stress fiber template

Abstract: Lamellar actin architecture at adhesion sites may serve as a structural template that facilitates focal adhesion maturation over a wide range of tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
310
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(368 citation statements)
references
References 52 publications
(114 reference statements)
54
310
3
1
Order By: Relevance
“…A similar dependence of shear tractions on substrate stiffness is predicted by the modelling framework used in the current study. It should be noted that, in the present study, significant tractions in the normal direction are where the cell has formed an approximately axisymmetric geometry, similar to that simulated here, the predicted orientations are found to be in agreement with experimentally observed dominant fibre bundles (Oakes et al 2012;Potter et al 1998) While the current study represents a step forward in the computational investigation of SF and FA behaviour of cells spread on elastic substrates, a number of limitations exist that should be considered in future studies. Experimental studies have shown that protrusion forces exerted by filopodia and lamellipodia during spreading can be ~ 5pN and ~20 pN (Cojoc et al 2007).…”
Section: Simulations Reveal Thatsupporting
confidence: 84%
See 1 more Smart Citation
“…A similar dependence of shear tractions on substrate stiffness is predicted by the modelling framework used in the current study. It should be noted that, in the present study, significant tractions in the normal direction are where the cell has formed an approximately axisymmetric geometry, similar to that simulated here, the predicted orientations are found to be in agreement with experimentally observed dominant fibre bundles (Oakes et al 2012;Potter et al 1998) While the current study represents a step forward in the computational investigation of SF and FA behaviour of cells spread on elastic substrates, a number of limitations exist that should be considered in future studies. Experimental studies have shown that protrusion forces exerted by filopodia and lamellipodia during spreading can be ~ 5pN and ~20 pN (Cojoc et al 2007).…”
Section: Simulations Reveal Thatsupporting
confidence: 84%
“…FA formation is modulated by traction forces on the adhesion and the size of the adhesion increases with force (Tan et al 2003;Balaban et al 2001). FAs are typically observed experimentally at the end of SF bundles (Burridge et al 1988) and disrupting SF contractility has been shown to cause FAs to disappear (Oakes et al 2012). Previous attempts to simulate FA dynamics have not considered the coupling between active SF contractility and FA assembly (Shemesh et al 2005;Bruinsma 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the speed of the patterning process is slow, making printing of large areas cumbersome and access to a specialized instrument is crucial. The two patterning methods are relevant for consideration because the size and shape of adhesive cue patterns influence the organization and distribution of biomechanical machineries that regulate cell migration 32,33 . Additionally, the limitation of the commercial microfluidic device employed here is that the channel length (1 μm) cannot be altered and so one cannot control the maximum steepness of the adhesive and soluble gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Pxn is used as the FA marker in this study, as its abundance in FAs is largely independent from myosin II activity 65 . This was used to generate a spatial mask to quantify and normalize local FAK activation as a function of myosin II activity, as has been done in previous studies 66,67 . An in-house built MATLAB script was used to quantify micrographs based on the morphometry and intensity of adhesions.…”
Section: Methodsmentioning
confidence: 99%